Assessment of Immunological Effects of Low-Level Er: YAG Laser Radiation - Ansari, Mojtaba; Rezaei-Tavirani, Mostafa; Hamzeloo-Moghadam, Maryam; Vafaee, Reza; Razzaghi, Mohhamadreza; Nikzamir, Mahfam; Rostami Nejad, Mohammad; Zamanizn Azodi, Mona (Journal of Lasers in Medical Sciences, 2022)
Introduction: Low-level laser radiation have a significant effect on cell proliferation. Various investigations about effect of Er: YAG laser on the treated cell lines are published. Determining of core targeted proteins is an attractive subject. Aim of this research is identifying the critical targeted protein by low-level Er: YAG laser in Primary Osteoblast-like Cells. Methods: Data was extracted from literature about proteomic assessment of 3.3 J/cm2 of low-level Er: YAG laser radiation on osteoblast-like cells of rat calvaria. The significant differentially expressed proteins (DEPs) plus 100 first neighbors were analyzed via network analysis and gene ontology enrichment. Results: Numbers of 9 DEPs among the 12 queried proteins were included in the main connected component. Analysis revealed that Cxcl1 is a key targeted protein in response to laser radiation. Presence of Cxcl1 in the significant cellular pathways indicates that cell growth and proliferation are affected. Conclusion: It can be concluded that Immune system is affected by laser to activate cellular defend against stress.